2020
DOI: 10.3390/w12092422
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Neonicotinoid Pesticides in Six Cultivable Fish Species from the River Owena in Nigeria and a Template for Food Safety Assessment

Abstract: The Owena River Basin in Nigeria is an area of agricultural importance for the production of cocoa. To optimise crop yield, the cocoa trees require spraying with neonicotinoid insecticides (Imidacloprid, Thiacloprid Acetamiprid and Thiamethoxam). It is proposed that rainwater runoff from the treated area may pollute the Owena River and that these pesticides may thereby enter the human food chain via six species of fish (Clariasgariepinus, Clariasanguillaris, Sarotherodongalilaeus, Parachannaobscura, Oreochromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Main (2019) traced the plight of the Japanese eel in 1993. Adegun et al (2020) identified neonics in six cultivable fish in the Owena River Basin by a QuEChERS/LC-tandem-MS method.…”
Section: Neonics As Insecticides and Their Dispersion In Ecosystemsmentioning
confidence: 99%
“…Main (2019) traced the plight of the Japanese eel in 1993. Adegun et al (2020) identified neonics in six cultivable fish in the Owena River Basin by a QuEChERS/LC-tandem-MS method.…”
Section: Neonics As Insecticides and Their Dispersion In Ecosystemsmentioning
confidence: 99%